(untitled) (Revista Contexto & Saúde, 2024)
Obstructive Sleep Apnea (OSA) is characterized by partial or total upper airways obstruction, resulting in intermittent hypoxia, oxyhemoglobin desaturation, and sleep fragmentation. Male gender and obesity are risk factors. The objective was to compare the performance of individuals with OSA to predicted values for knee extensor muscle strength, lower limb muscle endurance (LLME), and functional capacity. Additionally, the study aimed to examine the relationship between OSA severity and body mass index (BMI) with physical performance. This cross-sectional observational analytical study was conducted between October 2019 and June 2022, with eighteen men diagnosed with OSA. The instruments used were a digital dynamometer (maximum isometric voluntary contraction), a 30-second chair stand test, and a six-minute walk test. The sample had a mean age of 40.6 ± 9.2 years and BMI: 32.9 ± 7.6 kg/m². Knee extensor muscle strength did not differ compared to predicted values. LLME showed a trend towards reduction (12.8 ± 3.7 repetitions versus 15.2 ± 2.1 repetitions; p= 0.071; d=0.798), and functional capacity (p = 0.429; d = 0.177) did not significantly differ from predicted values. We concluded that individuals with OSA exhibit a statistical trend toward reduced LLME compared to predicted values. However, knee extensor muscle strength and functional capacity appear to be preserved. The Apnea-Hypopnea Index (AHI) is an independent predictor of functional capacity, and the AHI and BMI variables were directly correlated.